Nursing care for a patient after mastectomy in the home environment – nursing and psychosocial aspects - Maria Ciechacka (Quality in Sport)
Cancer is a disease of genetic material and develops as a result of the accumulation of gradually occurring genetic damage. The transformation of a normal cell into a cancer cell, known as neoplastic transformation, requires several gene mutations. In most cancers, DNA defects appear in the cells of individuals genetically predisposed to cancer development, under the influence of environmental factors that damage DNA, known as carcinogens.